Short Communication: Identification of Leptin gene in crossbred beef cattle - Laksa Ersa Anugratama; Tety Hartatik (Society for Indonesian Biodiversity, 2020)
Abstract. Anugratama LE, Hartatik T. 2020. Short Communication: Identification of Leptin gene in crossbred beef cattle. Biodiversitas 21: 226-230. Leptin is a gene that affects animal weight. Leptin gene is known to control body weight, feed intake, energy expenditure, immune function, and reproduction. This study aims to identify the diversity of the Leptin gene in crossbred beef cattle, Sumba Ongole cattle, Brahman cross cattle, Bali cattle, buffalo, sheep, and goat by comparing with four GenBank data of cattle. Crossbred beef cattle obtained from Klaten, Central Java, Indonesia. Leptin nucleotide sequences were analyzed using BioEdit to identify Single Nucleotide Polymorphism (SNP). To create amino acid change in Leptin gene, the coding sequence of exon 2 was established using BioEdit ver. 7.0.5. Phylogenetic tree and genetic distance have been analyzed based on the Leptin gene using MEGA 10.1.1 program. The result shows that eight variations of SNP were found in exon 2. The phylogenetic tree represents that crossbreed beef cattle, Sumba Ongole cattle, Brahman cross cattle, Bali cattle, Bos taurus, Bos indicus, Bos frontalis, Bos grunniens, Bubalus bubalis are in the same cluster with various genetic distance. The results of this study are expected to provide genetic information that will be used for further research on the relationship between Leptin gene polymorphisms to animal weight.